Dispute Resolution in Islamic Banking Industry Under The Iraqi Judiciary System - Salh , Shamsalden (المجلة الأكاديمية لجامعة نوروز, 2023)
Islamic banking transaction is based on an interest-free system that is prohibited to deal with riba. Several Islamic banks in Iraq are governed by the Central Bank of Iraq. Due to the lack of Islamic financial courts and lack of professional judges in the Islamic financial field, Islamic banking cases are handled by civil courts in Iraq. However, Islamic finance disputes should be considered by special courts with qualified judges in the field. The Judicial Authority in Iraq is not based on the Sharia system and the Sharia court specialised in Islamic finance in Iraq does not exist. As stated in Article 89 of the Iraqi Constitution of 2005 that the federal juridical power is comprised of the Higher Juridical Council, the Federal Supreme Court, the Federal Court of Cassation, the Public Prosecution Department, the Judiciary Oversight Commission, and other federal courts that are regulated under the law. Thus, Islamic banking disputes fall under the civil courts and the Courts of First Instance are responsible to handle cases of debt, and contracts. Furthermore, these courts are not specialists in Islamic banking and finance transactions. Therefore, a particular court, i.e. the Islamic financial court, should be among these courts in Iraq for resolving Islamic banking disputes. In addition, the special court has to include qualified judges who are familiar with Islamic finance.